Effects of the probiotic Lactiplantibacillus plantarum IMC 510® on body composition, biochemical parameters, gut microbiota composition and function, and clinical symptoms of overweight/obese subjects - Pagliai, Giuditta; Coman, Maria Magdalena; Baldi, Simone; Dinu, Monica; Nannini, Giulia; Russo, Edda; Curini, Lavinia; Colombini, Barbara; Lotti, Sofia; Pallecchi, Marco; Di Gloria, Leandro; Bartolucci, Gianluca; et al. (Frontiers in Nutrition, 2023)
Background and aim: In recent decades, obesity prevalence has reached epidemic proportions and considering the pivotal role of gut microbiota (GM) in the regulation of energy balance, alternative non-pharmacological approaches involving probiotics’ administration have been proposed. The aim of the present study was to evaluate the effect of Lactiplantibacillus plantarum IMC 510® supplementation on anthropometric and biochemical parameters, GM composition and functionality, and gastrointestinal and general symptoms of overweight/obese subjects. Methods: 40 overweight/obese subjects were randomly assigned to daily consume the probiotic Lactiplantibacillus plantarum IMC 510® or placebo for 3 months. Before and after the administration period, anthropometric and biochemical parameters, self-administered questionnaires and plasma and stool samples were obtained from each participant. The GM characterization was performed with 16S rRNA sequencing while faecal short (SCFAs) and medium (MCFAs) chain fatty acids were analysed with a gas chromatography-mass spectrometry protocol. Results: Compared to placebo, probiotic supplementation determined a significant decrease in body weight, BMI, waist circumference, waist-to-height ratio and blood glucose. Moreover, probiotic administration produced a significant decrease of the genera Hafnia-Obesumbacterium and Rombutsia and an increase of Succiniclasticum spp.; conversely, placebo administration resulted in the decrease of Actinomycetaceae and an increase of both Alloprevotella spp. and of the levels of proinflammatory hexanoic and heptanoic acids. Conclusions: Thanks to its effect in increasing some beneficial gut bacteria and lowering effects on waist circumference, fasting glucose levels and gastrointestinal symptoms of obese subjects, Lactiplantibacillus plantarum IMC 510® supplementation could represent a future and encouraging strategy for the prevention or treatment of obesity.